Pengaruh Pemberian Ramuan Jahe dan Temulawak terhadap Penurunan Nyeri Haid (Dysmenorea) - Keumalahayati Keumalahayati; Nuswatul Khaira; Fazdria Fazdria (Jurnal Keperawatan, 2018)
Menstruation is normal in a woman's life. The most common abnormalities are menstrual pain (dysmenorrhoea) and premenstrual syndrome. About one third of menstruating women will feel some pain that accompanies menstruation. The purpose of this study was to determine the effect of the effect of consuming ginger and ginger herbs on decreasing menstrual pain (dysmenorrhoe). The study design was quasi-experimental using the one group pretest-posttest design. The results of the study showed a significant difference in the intensity of menstrual pain before and after the ginger and ginger extract was administered, at a rate of 20: 20 grams compared to a 15: 15 gram dose. This can be seen from the p value obtained at 0,000 (p <0.05). The results of the study are expected to expand the area of ​​maternity nursing research for students regarding interventions to reduce menstrual pain in a nonpharmacological manner. For this reason, so that the use of ginger and ginger can be applied in the management of nursing care for women with primary dysmenorrhoea, further research is needed regarding the effectiveness of the management of dysmenorrhoea by utilizing ginger and ginger ingredients so that this action can be used as an alternative intervention.